Reposisi Praktik Ekonomi Islam: Studi Kritis Praktik Ekonomi Islam di Indonesia - Azwar Iskandar; Khaerul Aqbar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2019)
The study attempts to analyse several things that become critical points faced by Indonesia sharia economic practice that cause its application is less developed. This study use descriptive-qualitative approach with critical methode and library research. This research found that : (1) Sharia economy is not only financial sector but also includes the industrial sector, trade and various other real sector; (2) Naming ‘syariah bank’ is misleading. The appropriate nomenclature is not ‘syariah bank’ but syariah financial institution; (3) The attention of economic practioner both conventional and shariah, until now, only focused on achieving profit, protect loss, and welfare; (4) In the concept of Islam, the loss that faced by humans is caused apart from human factor and environment, it can also be caused by sin of business operators; (5) all moslem people and experts should not only concern on method of gain profit, but also encourage and promote people widely to commit the shariah rules in spending money; (6) The special education of syariah banking is needed by including it in universities and schools curriculum.